2018
DOI: 10.1016/j.ekir.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Nanotechnology-Based, Point-of-Care Diagnostic Device in Diabetic Kidney Disease

Abstract: IntroductionEarly detection of diabetes mellitus (DM) and diabetic kidney disease (DKD) is important for preventing end-stage renal failure and reducing cardiovascular complications. Availability of a validated point-of-care (PoC) device that can measure various DKD markers would be useful in this respect, especially in resource-poor parts of the world.MethodsWe validated a novel nanotechnology-based multianalyte PoC device (minimally invasive and does not require trained medical personnel) against laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Diabetes is a fast developing problem currently affecting millions of people worldwide [39]. It can lead to several serious complications such as lower limb amputations, blindness, cardiovascular diseases [39], and diabetic kidney disease [40]. Though diabetes has no cure, patients can reduce its complications by tightly monitoring and controlling the blood glucose levels [7, 39, 41].…”
Section: Various Nanosensors For Point-of-care Diagnosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetes is a fast developing problem currently affecting millions of people worldwide [39]. It can lead to several serious complications such as lower limb amputations, blindness, cardiovascular diseases [39], and diabetic kidney disease [40]. Though diabetes has no cure, patients can reduce its complications by tightly monitoring and controlling the blood glucose levels [7, 39, 41].…”
Section: Various Nanosensors For Point-of-care Diagnosticsmentioning
confidence: 99%
“…Though diabetes has no cure, patients can reduce its complications by tightly monitoring and controlling the blood glucose levels [7, 39, 41]. Early detection and strategies to prevent the progression of diabetes would make a big difference for the patients and would also be economically beneficial for a resource-constrained country [40]. Studies have shown that the control of blood glucose level in the normal range, commonly found in the range of 4.9–6.9 mM in healthy individuals, can help amelioration of microvascular (nephropathy, neuropathy, and retinopathy) and macrovascular (coronary artery disease and stroke) complications [7].…”
Section: Various Nanosensors For Point-of-care Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Kidney International Reports , Kumar et al. 9 reported on the clinical application of a nanotechnology-based multianalyte POC biosensor diagnostic device in Bangalore, India. The device was minimally invasive, could be used with minimal training, and was able to measure many of the critical variables important in the detection and management of diabetic kidney disease (glycosylated hemoglobin, hemoglobin, serum and urine albumin, urine creatinine, and the albumin-to-creatinine ratio).…”
mentioning
confidence: 99%
“…A large proof-of-concept and an even larger validation cohort make for reliable measurement results compared with gold standard laboratory results, as shown by the high correlation coefficients (R 2 > 0.8) and good linearity. It is expected that the use of devices (such as this POC device) in remote communities in underserved areas of the world, where the incidence and prevalence of diabetes mellitus and diabetic kidney disease continues to increase exponentially 9 and where delivery of care is woefully inadequate, will result in significant improvement in recognition and early management of diabetes and its complications. Deployment of inexpensive, simple devices such as this will exponentially increase the visibility of these problems and hopefully lead to implementation of measurable interventions that will affect the length and quality of millions of lives.…”
mentioning
confidence: 99%